Challenges and Opportunities of the Dynamic Operation of PEM Water Electrolyzers - Balázs Endrődi; Cintia Alexandra Trapp; István Szén; Imre Bakos; Miklós Lukovics; Csaba Janáky (Energies)
Hydrogen is expected to play an important role in decarbonizing different heavy industries and the transportation sector. Water electrolysis is, therefore, one of the most rapidly spreading energy technologies, with PEM electrolyzers taking a continuously increasing share in the technology mix. Most often, the aim is to form green hydrogen, utilizing electricity exclusively of renewable origin. The intermittency of such sources, however, poses several technological challenges and financial questions. Focusing on PEM electrolyzers, we discuss the effect of pressure, temperature, and reaction rate changes, induced by the intermittent operation, and general thoughts regarding system component erosion caused by the regular start–stop cycles are also considered. As a case study, we present a high-level techno-economic analysis of data from a pilot 1 MW PEM electrolysis system, coupled to a 20 MW PV farm, deployed in Hungary. We underscore the importance of the often overlooked local regulations and financial incentives, which strongly influence the most beneficial operation scenario.